Case Report: Gefitinib in EGFR 19del recurrent aggressive fibromatosis - Guo, Yanjing; Wu, Jingjing; Bai, Qianming; Wan, Juefeng; Wang, Qifeng; He, Xinhong; Zhang, Xiaowei; Luo, Zhiguo; Xing, Liju; Liu, Xin (Frontiers in Oncology, 2025)
We present the first case of a male patient with an epidermal growth factor receptor (EGFR) 19del mutation who was diagnosed with intra-abdominal aggressive fibromatosis and familial adenomatous polyposis. We assessed the clinical response of the patient to first-generation EGFR-tyrosine kinase inhibitors (EGFR-TKIs). A remarkable sustained partial response was achieved with the application of gefitinib after progression on multiple lines of therapy. The main adverse event of gefitinib treatment in this patient was a grade 2 rash. (Funded by the National Natural Science Foundation of China [Grant No. 82003061] and the Shanghai Sailing Program [20YF1408800] to Yanjing Guo, the Natural Science Foundation of Shanghai [Grant No. 24ZR1412800] to Xin Liu).